Efficacy and tolerability of mirabegron in female patients with overactive bladder symptoms after surgical treatment for stress urinary incontinence - Özkidik,Mete (2019)
ABSTRACT Purpose To evaluate the efficacy and tolerability of mirabegron in females with overactive bladder (OAB) symptoms after surgical treatment for stress urinary incontinence (SUI). Materials and Methods The study was conducted with a prospective, randomized and double-blinded design. 62 patients over the age of 40 who met the inclusion-exclusion criterias of the study were enrolled and randomly divided into two groups as Group A (mirabegron 50mg) and B (solifenacin 5mg). Patients were compared based on efficacy of treatment [Patient Perception of Bladder Condition (PPBC) scale and micturition diaries], safety of treatment (heart rate, systolic and diastolic blood pressure, adverse events), number of micturitions per day, patient’s satisfaction status after treatment [Visual Analog Scale(VAS)] and quality of life. Results The mean age of the population was 48.2±3.8 years and the duration of OAB symptoms was 5.9±2.9 months. Baseline values for the mean number of micturitions, volume voided in each micturition, nocturia episodes, urgency and urgency incontinence episodes were 15.3±0.34, 128±3.88mL, 3.96±1.67, 5.72±1.35 and 4.22±0.69, respectively. After treatment, values for these parameters were 11.7±0.29, 164.7±2.9mL, 2.25±0.6, 3.38±0.71, 2.31±0.49 respectively. Quality of life score, symptom bother score, VAS for treatment satisfaction score, PPBC score after treatment were 66.1±0.85, 43.7±0.77, 4.78±0.14, 4.78±0.14, respectively. There were no significant differences between two groups on any parameter. However, mirabegron showed better tolerability than solifenacin, particularly after 6 months. Conclusion Mirabegron is safe, effective and tolerable in the long-term treatment of females with OAB symptoms after surgery for stress urinary incontinence.